Yield of Water as an Element in Multiple Use of Wild Land - Connaughton, Charles A. (Indian Forester, 1944)
Service as watersheds is one of the most important contributions that wild mountain lands make to the economy of the semiarid West. Their utility for watershed purposes is influenced by a number of factors, of which those associated with the kind and density of vegetation may be manipulated in coordination with other uses to obtain optimum yields of usable water. Since the benefits of land management for water yield may often be less direct than the returns from other resources, land managers are cautioned to guard against subordinating watershed services to other uses at the expense of the public welfare.